(untitled) - Nida, Eugene Albert; (1914-2011) (U.S.A, 1949)
This book is designed especially for missionaries. Accordingly, the illustrations of linguistic problems are drawn principally from languages with which missionaries are primarily concerned and from the actual experience that missionaries have had with these languages.
Keywords: Learn foreign languages